Polypharmacy and adverse drug events among propensity score matched privately insured persons with and without spinal cord injury. Issue 6 (June 2018) - Hand, Brittany; Krause, James; Simpson, Kit
Abstract Study design Retrospective quasi-experimental design. Objectives To compare the incidence of adverse drug events (ADEs) between persons with and without spinal cord injury (SCI), while controlling for all potential and available risk factors. Setting A commercially available claims dataset consisting of ~170 million patient cases in the United States between 2012 and 2013. Methods Participants (aged 18–64 years) included 2779 persons with polypharmacy and traumatic or non-traumatic SCI and 2779 propensity score-matched persons with polypharmacy without SCI. The cohorts were matched using demographic variables including number of concomitant prescriptions, comorbidities, hospital admissions, age, gender, and geographic region. Inpatient and outpatient claims records containing 395 distinct IDC-9 codes indicative of ADEs were extracted. Incidence and frequency of ADEs were compared between groups using logistic and Poisson regression, respectively. Results Persons with SCI were significantly more likely to experience an ADE than matched controls (Odds Ratio = 1.45, p  < 0.0001). Among persons with ADEs (n  = 1552), individuals with SCI experienced fewer ADEs over time than matched controls (Incidence Rate Ratio = 0.91, p  < 0.0001). Conclusions While persons with SCI and polypharmacy are at a greater risk for experiencing an ADE, their medical care after an ADE may be better managed than that of a matched control population. There may be a need for practice guidelines that facilitate proactive identification of persons with SCI at the highest risk of ADE. Steps may then be taken to mitigate risk, in contrast to current practice trends that appear to take a reactive approach after an ADE has occurred.